Mengubah Limbah Menjadi Eco-Enzim: Strategi Efektif Menghadapi Limbah Sayur Dan Buah Di Pasar Raya MMTC Medan - Ellma Aggresia Br Purba; Dhea Zuhrika; Fadila Khoiri; M. Hayqal Adibya; Meilinda Suriani Harefa (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
People throw away rubbish every day without stopping. Garbage disposal increases the amount of organic and inorganic waste. Organic waste comes from plants such as vegetables and fruit. Currently inorganic waste comes from plastic, bottles and household furniture. Until now, waste processing has not been optimal, but there is waste that can be processed into something useful and of economic value. Limited knowledge and lack of skills are obstacles in waste disposal. Therefore, waste processing efforts are needed, such as processing organic waste into eco-enzymes. This research uses a literature review method.